Toys Galore - Stein, Peter (Peter Lawrence); Staake, Bob, 1957- (Somerville, Massachusetts : Candlewick Press, 2013)
The world's wackiest toy chest features toys of all shapes and sizes, plus the best toy of all, one's imagination.
new kids book 2023 fall.
Keywords: Toys -- Juvenile fiction; Imagination -- Juvenile fiction; Play -- Juvenile fiction; Toys -- Fiction; Imagination -- Fiction; Play -- Fiction; Stories in rhyme